Penerapan Sistem Dwi Partai dan Multi Partai pada Calon Pasangan Presiden dan Wakil Presiden berdasarkan Pasal 6A Ayat (2) Undang – Undang Dasar 1945 - Firman Pratama (UNISBA Press, 2022)
Abstract. The promotion of presidential and vice presidential candidates by political parties in Indonesia is influenced by a bi-party and multi-party system. The party system that emerged as a consequence of a democratic state, but in Indonesia the rapid change of power affected both systems. The Old Order introduced multi-party known as the pattern of the parliamentary system, the New Order introduced a bi-party system with a presidential system, the Reform Order with a multi-party system with a presidential system. This situation is facilitated by Article 6(A) paragraph (2) of the 1945 Constitution in determining the ability of political parties to carry presidential and vice presidential candidates. The research method used in this study is the normative juridical method, which is a legal research method carried out by examining library materials or secondary data. Submission of presidential and vice presidential candidates in Indonesia can be done through a combined mechanism of political parties in a multi-party system that can submit candidates for residents through a multi-party system. The system of party muli and dual parties had been implemented before the Reform order, precisely in the Old Order and the New Order. Abstrak. Pengusungan calon presiden dan wakil calon presiden oleh partai politik di Indonesia dipengaruhi oleh sistem dwi partai dan multi partai. Sistem kepartaian yang muncul sebagai konsekunesi negara demokrasi, akan tetapi di Indonesia perubahan yang cepat dari kekuasaan mempengaruhi kedua sistem tersebut. Orde Lama mengenalkan multi partai dikenal dengan corak sistem parlementer, Orde Baru mengenalkan sistem dwi partai dengan sistem presidensial, Orde Reformasi dengan sistem multi partai dengan sistem presidensial. Keadaan ini coba difasilitasi oleh Pasal 6(A) ayat (2) Undang-Undang Dasar 1945 dalam menentukan kemampuan partai politik untuk mengusung calon presiden dan wakil calon presiden. Metode penelitian yang digunakan dalam penelitian ini adalah metode yuridis normatif yaitu metode penelitian hukum yang di lakukan dengan meneliti bahan pustaka atau data sekunder. Pengajuan calon presiden dan wakil presiden di Indonesia dapat dilakukan melalui mekanisme gabungan partai politik dalam sistem multi partai yang dapat mengajukan pencalonan prsiden melalui sistem multi partai. Sistem muli partai dan dwi partai telah diterapkan sebelum Orde Reformasi, tepatnya pada Orde Lama dan Orde Baru.